Microbial community structure dynamics of invasive bullfrog with meningitis-like infectious disease - Li, Wengang; Fan, Guangwei; Sun, Ke; Liu, Jingru; Liu, Jinyan; Wang, Yu; Li, En; Wu, Xiaobing; Shen, Liang; Pan, Tao (Frontiers in Microbiology, 2023)
Abstract: Meningitis-like infectious disease (also known as frog cataract and torticollis) is a disease prone to occur in amphibians and reptiles. It is highly contagious and has a high mortality rate. In this study, we sampled and sequenced microbiomes from oral and intestinal samples of five normal and five diseased bullfrogs. The analysis found that the richness, uniformity, and abundance of the microbial community of the diseased bullfrogs were significantly higher than those of the normal bullfrogs in both the oral cavity and the gut. In the diseased group, the abundance of Elizabethkingia significantly increased and that of Lactococcus significantly decreased. It showed that the structure of the microbial community had changed a lot in diseased frogs. After the pathogenic bacteria infected the body, it might be make the decline in the immune function of the body declined, and resulting in some conditional pathogenic bacteria in the water body further infecting the body. As a result, the richness and composition of the microbial community significantly changed. This study can provide a theoretical basis for the control of MID of bullfrogs.